Biotechnology of Natural Products (Springer International Publishing, 2018)
This text comprehensively covers the analysis, enzymology, physiology and genetics of valuable natural products used in the food industry that are attractive targets for biotechnological production. The focus is on the recent advances made to achieve this goal. This unique work is the first book to focus on biotechnological production of important natural products in food additives, fragrances and flavorings, and other bioactive compounds in food. The chapters offer a deep insight into modern research and the development of low molecular weight natural products. Biotechnology of Natural Products covers products in the Phenolic, Terpenoid, and Alkaloid categories, providing a full overview of the biotechnology of food additives and other low molecular weight natural products. Gene clustering and the evolution of pathways are covered, as well as future perspectives on the topic. Due to limited oil resources and increasing consumer demand for naturalness, bioprocesses are increasingly needed to meet these requirements. Novel sophisticated technologies have facilitated the elucidation of new chemical molecules, their biosynthetic pathways and biological functions. This book provides researchers with a full overview of the technologies and processes involved in the biotechnology of natural products. .